Ideal Cardiovascular Health and Arterial Stiffness in Spanish Adults—The Evident Study - Garcia-Hermoso, A (W.B. Saunders, 2018)
Background: Studies concerning ideal cardiovascular (CV) health and its relationship with arterial stiffness are lacking. This study examined the association between arterial stiffness with ideal CV health as defined by the American Heart Association, across age groups and gender. Methods: The cross-sectional study included 1365 adults. Ideal CV health was defined as meeting ideal levels of the following components: 4 behaviors (smoking, body mass index, physical activity, and Mediterranean diet adherence) and 3 factors (total cholesterol, blood pressure, and glycated hemoglobin). Patients were grouped into 3 categories according to their number of ideal CV health metrics: ideal (5-7 metrics), intermediate (3-4 metrics), and poor (0-2 metrics). We analyzed the pulse wave velocity (PWV), the central and radial augmentation indexes, and the ambulatory arterial stiffness index (AASI). Results: The ideal CV health profile was inversely associated with lower arterial radial augmentation index and AASI in both genders, particularly in middle-aged (45-65 years) and in elderly subjects (>65 years). Also in elderly subjects, adjusted models showed that adults with at least 3 health metrics at ideal levels had significantly lower PWV than those with 2 or fewer ideal health metrics. Conclusions: An association was found between a favorable level of ideal CV health metrics and lower arterial stiffness across age groups. © 2018 National Stroke Association
Keywords: Ambulatory arterial stiffness index; Health behaviour; Health factors; Pulse wave velocity